A kinetic model for the ultrasound catalyzed hydrolysis of solventless TEOS-water mixtures and the role of the initial additions of ethanol - Vollet, D. R.; Donatti, D. A.; Campanha, JR (Kluwer Academic Publ, 1996)
The acid and ultrasound catalyzed hydrolysis of solventless TEOS-water mixtures are studied, as a function of the initial additions of ethanol to the mixtures, by means of flux calorimetry measurements. A device was specially designed for this purpose. Under acid conditions, our proposed method has been able to resolve hydrolysis from other condensation reactions, by detecting the exothermal hydrolysis reaction heat. The process has been explained by a dissolution and reaction mechanism. Ultrasound forces the dissolution process to start the reaction. The alcohol produced in the reaction helps the dissolution process to further enhance the hydrolysis. Initial amounts of pure ethanol added to the mixtures shorten the start time of the reaction, due to an additional effect of dissolution, and diminish the reaction rate, as a result of the solvent dilution effect. Our dissolution and reaction mechanism modeling describes the main points arising from the experimental data and yields k(H) = 0.24 M(-1) min(-1) for the second-order hydrolysis rate constant at 39 degrees C.
Keywords: hydrolysis; TEOS; calorimetry; ethanol additions